2019
DOI: 10.1177/0269881119841568
|View full text |Cite
|
Sign up to set email alerts
|

Dissociable effects of cannabis with and without cannabidiol on the human brain’s resting-state functional connectivity

Abstract: Background: Two major constituents of cannabis are D 9-tetrahydrocannabinol (THC) and cannabidiol (CBD). THC is the main psychoactive component; CBD may buffer the user against the harmful effects of THC. Aims: We examined the effects of two strains of cannabis and placebo on the human brain's resting-state networks using fMRI. Methods: 17 healthy volunteers (experienced with cannabis, but not regular users) underwent three drug treatments and scanning sessions. Treatments were cannabis containing THC (Cann-CB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
63
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 61 publications
(97 reference statements)
9
63
0
1
Order By: Relevance
“…To our knowledge, our work provides the first demonstration of THC’s effects on mind wandering during a concurrent cognitive task. These finding are consistent with prior work on THC, including task-independent reports of mind wandering in structured interviews [ 86 , 87 ], failure to de-activate the default mode network during task performance [ 88 ] (but see [ 89 ]), and decreased error monitoring [ 42 , 43 , 90 ]. Similar to the effects of nicotine cravings [ 40 ] and alcohol [ 41 ], THC appears to increase mind wandering and other off-task mental states (e.g., “zoning out” or “mind blanking” [ 55 ]), and decrease awareness of task performance.…”
Section: Discussionsupporting
confidence: 89%
“…To our knowledge, our work provides the first demonstration of THC’s effects on mind wandering during a concurrent cognitive task. These finding are consistent with prior work on THC, including task-independent reports of mind wandering in structured interviews [ 86 , 87 ], failure to de-activate the default mode network during task performance [ 88 ] (but see [ 89 ]), and decreased error monitoring [ 42 , 43 , 90 ]. Similar to the effects of nicotine cravings [ 40 ] and alcohol [ 41 ], THC appears to increase mind wandering and other off-task mental states (e.g., “zoning out” or “mind blanking” [ 55 ]), and decrease awareness of task performance.…”
Section: Discussionsupporting
confidence: 89%
“…Decreases in DMN sFC during the acute effects of hallucinogens have been a replicable finding, occurring with psilocybin 30,34 , LSD 25,35 , DMT 33 , and ketamine 31,32 . Although it might be tempting to speculate that these effects reflect "ego dissolution" 30,40 , decreases in sFC within the DMN have also been observed with acute administration of drugs not typically associated with ego dissolution such as THC 62 , alcohol 63 , and amphetamine 64 . The small samples, short scan times, numerous reports based on single datasets, underreporting of comparable or larger effects on other brain networks, and inconsistency across studies between brain measures and ego dissolution undermine the strength of reverse inferential claims regarding the specificity of DMN effects to ego dissolution.…”
Section: Discussionmentioning
confidence: 99%
“…176,177 Human research has shown that THC intake resulted in decreases in the default mode network activation (a large scale of interacting brain regions known to have activity highly correlated with each other, especially during task disengagement 178 ), whereas a combination of THC and CBD attenuated the disruption in this network seen when THC is taken alone. 179 Patients with autism spectrum disorder were administered 600 mg of CBD and they also showed changes in functional connectivity as assessed by the fractional amplitude of low-frequency fluctuations. 180 While the direct underlying mechanism by which CBD regulates functional connectivity requires more research, there is a clear therapeutic effect on functional connectivity following CBD intake.…”
Section: Cerebrovasculaturementioning
confidence: 99%